Observation of kagome-like bands in two-dimensional semiconducting Cr8Se12 - Sisheng Duan; Jing-Yang You; Zhihao Cai; Jian Gou; Dong Li; Yu Li Huang; Xiaojiang Yu; Siew Lang Teo; Shuo Sun; Yihe Wang; Ming Lin; Chun Zhang; et al. (Nature Communications)
Abstract The kagome lattice is a versatile platform for investigating correlated electronic states. However, its realization in two-dimensional (2D) semiconductors for tunable device applications is still challenging. An alternative strategy to create kagome-like bands is to realize a coloring-triangle (CT) lattice in semiconductors through a distortion of a modified triangular lattice. Here, we report the observation of low-energy kagome-like bands in a semiconducting 2D transition metal chalcogenide—Cr8Se12 with a thickness of 7 atomic layers—which exhibits a CT lattice and a bandgap of 0.8 eV. The Cr-deficient layer beneath the topmost Se-full layer is partially occupied with 2/3 occupancy, yielding a √3 × √3 Cr honeycomb network. Angle-resolved photoemission spectroscopy measurements and first-principles investigations reveal the surface kagome-like bands near the valence band maximum, which are attributed to topmost Se p z orbitals modulated by the honeycomb Cr.